Introgressive Hybridization and Hypoxia Adaptation in High-Altitude Vertebrates - Storz, Jay F.; Signore, Anthony V. (Frontiers in Genetics, 2021)
In natural populations of animals, a growing body of evidence suggests that introgressive hybridization may often serve as an important source of adaptive genetic variation. Population genomic studies of high-altitude vertebrates have provided strong evidence of positive selection on introgressed allelic variants, typically involving a long-term highland species as the donor and a more recently arrived colonizing species as the recipient. In high-altitude humans and canids from the Tibetan Plateau, case studies of adaptive introgression involving the HIF transcription factor, EPAS1, have provided insights into complex histories of ancient introgression, including examples of admixture from now-extinct source populations. In Tibetan canids and Andean waterfowl, reverse-genetics experiments involving introgressed hemoglobin variants successfully identified causative amino acid mutations and characterized their phenotypic effects, thereby providing insights into the functional properties of selectively introgressed alleles. We review case studies of adaptive introgression in high-altitude vertebrates and we highlight findings that may be of general significance for understanding mechanisms of environmental adaptation involving different sources of genetic variation.